Power Transformer Loading Analysis in Order to Improve the Reliability of a Substation - Syahputra, Ramadoni; Arrozak, Loudy Fajar (Journal of Electrical Technology UMY, 2017)
This paper presents the power transformer loading analysis in order to improve the reliability of a substation. The substation that was the location of the study was the 150/20 KV Kentungan Substation, Sleman, Yogyakarta Special Region. Power transformers are the most important electrical equipment in a substation. The power transformer functions as a provider of electrical energy that has been transmitted from the power plant to then be channeled to electricity loads. In its operational it is very important to know the capacity and capacity of power transformers in serving electric loads for decades to come, with the aim that the electric power service can take place well. Therefore, the forecasting of the power transformer is important to know in the framework of the operational planning of a good substation. The results of the study indicate that the peak load of power transformers in the period 2014 to 2016 is still in a safe level, where the maximum peak load is 93% of the total capacity of the transformer. However, it is recommended that the power transformer capacity be planned to begin to anticipate the growth of loads in the coming years.